Novel PIP5K1C variant identified in a Chinese pedigree with lethal congenital contractural syndrome 3 - Fang Zhang; Hongmei Guo; Xinlong Zhou; Zhengxi Deng; Qiuhong Xu; Qingming Wang; Haiming Yuan; Jianhua Luo (BMC, 2024)
Abstract Background Biallelic pathogenic variants in PIP5K1C (MIM #606,102) lead to lethal congenital contractural syndrome 3 (LCCS3, MIM #611,369), a rare autosomal recessive genetic disorder characterized by small gestational age, severe multiple joint contractures and muscle atrophy, early death due to respiratory failure. Currently, 5 individuals with LCCS3 were reported and 5 pathogenic variants in PIP5K1C were identified. Here, we reported the two fetuses in a Chinese pedigree who displayed multiple joint contractures and other congenital anomalies. Methods Trio-based whole-exome sequencing (WES) was performed for the parents and the recent fetus to detect the genetic cause for fetus phenotype. Results A novel variant, NM_012398.3: c.949_952dup, p.S318Ifs*28 and a previously reported variant, c.688_689del, p.G230Qfs*114 (ClinVar database) in PIP5K1C, were detected in the individuals, and these variants were inherited from the mother and father, respectively. We described the features of multiple joint contractures in our fetuses, including bilateral talipes equinovarus, stiffness in the limbs, extended knees, persistently closed hands and overlapping fingers, which have not been delineated detailedly in previously reported LCCS3 individuals. Furthermore, novel phenotype, bilateral dilated lateral ventricles, was revealed in one fetus. Conclusions These findings expanded the genetic variant spectrum of PIP5K1C and enriched the clinical features of LCCS3, which will help with the prenatal diagnosis and genetic counseling for this family.